Efficacy and safety of subcutaneous administration of ceftazidime as a salvage therapy in geriatrics: a case report. (25th November 2019) - Michelon, Hugues; Tardivel, Marie; Dinh, Aurélien; Alvarez, Jean‐Claude; Salomon, Elsa; Le Quintrec, Jean‐Laurent; Hirt, Deborah; Davido, Benjamin
Abstract: Ceftazidime is a third‐generation cephalosporin used for the treatment of Gram‐negative bacteria only approved for parenteral use by intravenous and intramuscular route. In some clinical situations, off‐label subcutaneous injection could be a salvage route for the administration of antibiotics, especially in geriatrics, despite the paucity of evidence about efficacy and safety. We report a case of a successful and well‐tolerated subcutaneous ceftazidime therapy in a 90‐year‐old woman for the treatment of an acute urinary tract infection caused by Pseudomonas aeruginosa with therapeutic drug monitoring data.